Modern Methods Of Glucose Monitoring In The Context Of Physical Activity - Review Study - Aleksandra Jędrasek; Tomasz Jędrasek; Julia Pogoda; Jan Piotrowski; Izabela Hądzlik; Julia Biały-Karbowniczek; Katarzyna Słychan; Blanka Łuczak; Klaudia Bulska; Konrad Sławek (Nicolaus Copernicus University in Toruń, 2024)
Introduction: In the last few years, with over 422 million cases of diabetes worldwide and with an overload of healthcare, the development of new glucose monitoring approaches has become a crucial subject. This paper set out to explore the effectiveness of current glucose monitoring methods, their usage in the context of physical activity, and prospects for the future. Review methods: We conducted our study as a literature review, with data being gathered via PubMed and Embase. The state of knowledge: Currently, the two most popular methods of glucose monitoring are self-monitoring (SMBG) and continuous glucose monitoring (CGM) with real-time devices such as Dexcom G6, and Medtronic Guardian Connect System, and intermittent devices such as Freestyle Libre 2. Both approaches are invasive and can cause allergic reactions and dermatitis. As a result, many researchers propose non-invasive methods including optical coherence tomography, spectroscopy, and fluorescence. The growing accessibility leads to the usage of CGM devices in everyday life not only by patients with diabetes melitus.  Conclusions: Advancements in diabetes technologies allow patients to maintain glucose homeostasis and improve their Quality of life. CGM devices are constantly being developed to be more accessible and easy to use, which may help adjust the training programs and diets for individual needs.